Nikiah Ray: capstone - Ray, Nikiah, artist (Colorado State University. Libraries, 2024)
The artist's statement: This body of work has been developed and formulated over multiple years. It started off as an analysis of how my family influences my own personal self-identification then gradually moved onto how outside factors influence my self-expression. The work was made from long exposure, capturing the movements of the subject. The subject is expressing how they feel while listening to music. Music has been an important aspect to discovering myself and been something that lets me express myself in the best way possible. This series is a representation of what music can do for the mind.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making